A Case Report of a Patient with Soaring Clozapine Levels after Developing a Urinary Tract Infection - Adesh Kumar Agrawal; Soumitra Das; Lorenzo Abednego B. Adre; Nakka Raghuma; Sharanya Kaushik; Adarsha Adhikari (Case Reports in Psychiatry)
Clozapine is an antipsychotic medicine used to treat mental illnesses that is resistant to therapy. It can induce dose-dependent adverse effects such as increased susceptibility to infections and hematological irregularities. In this case report, we present a 37-year-old woman with schizoaffective disorder who experienced clozapine side effects following a moderate urinary tract infection (UTI). Her serum clozapine levels and side effects were increased throughout her UTI but resolved once the UTI was managed conservatively. We reviewed clozapine’s pharmacokinetic properties to understand why serum levels rose during infection. While we could not definitely explain the mechanism of elevation, we emphasize the importance of monitoring serum clozapine levels and keeping watchful for adverse effects, as well as heightened scrutiny, evaluation for recent infections, and regular monitoring of patients.